Dislocation of the metacarpophalangeal joint: a narrative review treatment and examination - Malisorn, Saran (International Journal of Research in Orthopaedics, 2023)
The dislocation of the metacarpophalangeal (MCP) joint is complex, often occurs due to complications from excessive stretching or overextension that cannot be reduced. The volar plate moves to back of the head metacarpal bone and the base of the proximal phalanx that is near the proximal phalanx, acting as an obstruction to the contraction. Although it is true that pathophysiology is relatively complex, the resulting damage is not normal, and the reduction of such damage often depends on experience. Present a case of a complex fracture of the MCP joint, along with a review of the literature on the anatomical relationship and therapeutic armamentarium.